CETUS: A SOURCE-TO-SOURCE COMPILER INFRASTRUCTURE FOR MULTICORES. - Dave, Chirag; Hansang Bae; Seung-Jai Min; Seyong Lee; Eigenmann, Rudolf; Midkiff, Samuel (Computer (00189162), 2009)
The article discusses the Cetus tool, a compiler infrastructure which supports source-to-source transformations. Cetus targets C programs and can be compared with Intel's ICC compiler and the COINS research compiler. Cetus enables autoparallelization and its framework reveals that it is state of the art. However, it has a longer compilation time than an industrial compiler.